The work values and job involvement of Post-80s employees in the hospitality and tourism industry: empirical evidence from Macau. Issue 2 (3rd April 2019) - Chan, Sow Hup Joanne; Kong, Siew Huat; Lei, Chon Kit
Abstract: The purpose of this research was to examine the work values (WV) and the job involvement (JI) of the younger workforce in a Chinese society. Specifically, the study explores the case of Macau, which has transformed from a sleepy enclave to a gambling mecca. The findings from 384 full-time Chinese employees revealed four WV factors considered important to them. The Post-80s value the social environment and freedom. WV are significantly positively correlated with JI and vary significantly across demographic variables. Intrinsic WV have prediction power towards JI. The lack of research on the younger generation particularly in this popular tourism destination contribute to a better understanding and management of the workforce. It also highlights that traditional Chinese managerial practice might not be able to cope with the new expectations and work habits of the younger workers.